The Effects of Tormentic Acid and Extracts from Callistemon citrinus on Candida albicans and Candida tropicalis Growth and Inhibition of Ergosterol Biosynthesis in Candida albicans - Chido Bvumbi; Godloves Fru Chi; Marc Y. Stevens; Molly Mombeshora; Stanley Mukanganyama (The Scientific World Journal)
Candida albicans and Candida tropicalis are the leading causes of human fungal infections worldwide. There is an increase in resistance of Candida pathogens to existing antifungal drugs leading to a need to find new sources of antifungal agents. Tormentic acid has been isolated from different plants including Callistemon citrinus and has been found to possess antimicrobial properties, including antifungal activity. The study aimed to determine the effects of tormentic and extracts from C. citrinus on C. albicans and C. tropicalis and a possible mode of action. The extracts and tormentic acid were screened for antifungal activity using the broth microdilution method. The growth of both species was inhibited by the extracts, and C. albicans was more susceptible to the extract compared to C. tropicalis. The growth of C. albicans was inhibited by 80% at 100 μg/ml of both the DCM: methanol extract and the ethanol: water extract. Tormentic acid reduced the growth of C. albicans by 72% at 100 μg/ml. The effects of the extracts and tormentic acid on ergosterol content in C. albicans were determined using a UV/Vis scanning spectrophotometer. At concentrations of tormentic acid of 25 μg/ml, 50 μg/ml, 100 μg/ml, and 200 μg/ml, the content of ergosterol was decreased by 22%, 36%, 48%, and 78%, respectively. Similarly, the DCM: methanol extract at 100 μg/ml and 200 μg/ml decreased the content by 78% and 88%, respectively. A dose-dependent decrease in ergosterol content was observed in cells exposed to miconazole with a 25 μg/ml concentration causing a 100% decrease in ergosterol content. Therefore, tormentic acid inhibits the synthesis of ergosterol in C. albicans. Modifications of the structure of tormentic acid to increase its antifungal potency may be explored in further studies.